Overview of Ear, Nose, and Throat Complaints of Covid 19 Inpatients at the University of Muhammadiyah Malang Hospital for the Period April 2021 to June 2021 - Nimim Putri Zahara; Jauhar Tajudin; Indra Setiawan (Universitas Muhammadiyah Malang, 2022)
Covid-19 is spreading rapidly to other countries, and WHO confirmed it as a pandemic disease in March 2020. The virus enters directly to the surface of the mucosa with a high viral load, so it is clear that complaints in the nose and throat area are found. Covid-19 initially appears mainly in the airway with symptoms can be fever and dyspnea cough which can quickly switch to acute respiratory distress syndrome. RSU Universitas Muhammadiyah Malang has been one of the Covid-19 referral hospitals in East Java since April 2020, and there is no data on the description of nasal ear and throat complaints (ENT) in Covid-19 hospitalization patients at UMM Hospital. Mengetahui overview and overview of nose and throat ear complaints (ENT) experienced by Covid-19 hospitalized patients at UMM Hospital in the period April 2021 to June 2021. Descriptive retrospectively by taking data from the medical records of Covid-19 hospitalization patients of UMM Hospital in the period April to June 2021 with a total sampling method of 161 hospitalized patients with a confirmed diagnosis of Covid-19 with PCR examination during the period of April to June 2021. The study was conducted on 161 medical records with the results of 84 patients were men with 21 patients with severe degrees, 63 patients with moderate degrees, and 77 patients were women with 18 patients with severe degrees and 59 patients with moderate degrees. Mortality rates were obtained in as many as 26 (16%) with varying age ranges; 78 (48%) patients had comorbidities, with Diabetes mellitus as the highest comorbid among as many as 31 (40%) patients. Patients with ENT complaints were obtained among as many as 95 (60%) patients, and 66 (40%) patients were not accompanied by ENT complaints. The three most ENT complaints were colds (rhinitis) in as many as 62 (39%) patients, anosmia hyposmia in as many as 26 (16%) patients, and throat pain in as many as 22 (14%) patients. Most patients were men with moderate degrees, with mortality rates of 16% and 48% of patients accompanied by comorbidities. The most ENT complaints were rhinitis 39%, anosmia-hyposmia 16%, and throat pain in as much as 14% of patients.